2017
DOI: 10.1002/jbm.b.33902
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of wear debris from metal‐on‐metal hip implants during normal wear versus edge‐loading conditions

Abstract: Advantages of second-generation metal-on-metal (MoM) hip implants include low volumetric wear rates and the release of nanosized wear particles that are chemically inert and readily cleared from local tissue. In some patients, edge loading conditions occur, which result in higher volumetric wear. The objective of this study was to characterize the size, morphology, and chemistry of wear particles released from MoM hip implants during normal (40° angle) and edge-loading (65° angle with microseparation) conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…It is possible that HRs elicit more easily an immunologic neosynovitis type reaction, whereas the coarser taper wear in THAs is associated with wear‐type synovial responses, namely “foreign‐body,” “necrotic,” and “inflammatory lymphocytic” neosynovitis. It should be, however, noted that as recent simulator study showed HRs with edge loading and microseparation produce larger and coarser wear particles, possibly even larger extracellular particles, compared with more normal wear conditions (Kovochich et al, ). Hence “foreign‐body,” “necrotic,” and “inflammatory lymphocytic” neosynovitis are observed in HRs also.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is possible that HRs elicit more easily an immunologic neosynovitis type reaction, whereas the coarser taper wear in THAs is associated with wear‐type synovial responses, namely “foreign‐body,” “necrotic,” and “inflammatory lymphocytic” neosynovitis. It should be, however, noted that as recent simulator study showed HRs with edge loading and microseparation produce larger and coarser wear particles, possibly even larger extracellular particles, compared with more normal wear conditions (Kovochich et al, ). Hence “foreign‐body,” “necrotic,” and “inflammatory lymphocytic” neosynovitis are observed in HRs also.…”
Section: Discussionmentioning
confidence: 98%
“…It should be, however, noted that as recent simulator study showed HRs with edge loading and microseparation produce larger and coarser wear particles, possibly even larger extracellular particles, compared with more normal wear conditions (Kovochich et al, 2018). Hence "foreign-body," "necrotic," and "inflammatory lymphocytic" neosynovitis are observed in HRs also.…”
Section: Validation Analysismentioning
confidence: 96%
“…Furthermore, animal joints such as the canine hip implant were considered [378]. While the main focus of the present joint tribology was on the engineering aspects of biotribology, a number of clinical and biological studies were also found [379,380]. Tribological effects at cellular levels [381,382] and on regenerative ability [383] were also found to be increasingly examined.…”
Section: Joint Tribologymentioning
confidence: 99%
“…We utilized a cobalt-chromium-molybdenum (CoCrMo) particle-induced mouse calvarial osteolysis model to directly evaluate the effects of PF against localized particle-induced osteolysis. The CoCrMo particles had an average diameter of 100 nm ( Figure 4B ), which was reported to be clinically relevant [ 28 ]. We found that cranium osteolysis was much more extensive in CoCrMo-treated mice than in control mice, as shown by μ-CT 3D reconstruction ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%